Long noncoding RNA MIR155HG facilitates pancreatic cancer progression through negative regulation of miR‐802. Issue 10 (3rd June 2019) - Qin, Yan; Liu, Xin; Pan, Liang; Zhou, Rong; Zhang, Xiaoping
Abstract: Long noncoding RNAs (lncRNAs) present the key regulatory functions in tumorigenesis. More and more studies have suggested that lncRNA MIR155HG is involved in different human cancers. However, the underlying regulatory role of lncRNA MIR155HG and potential mechanisms in pancreatic cancer (PC) remain illusive. In this research, our group found that lncRNA MIR155HG expression was remarkably increased in PC tumor tissue and cells compared to that in the adjacent normal tissue and cells. In addition, higher MIR155HG expression was positively associated with the poor prognosis of patients. In addition, we exhibited that silence of MIR155HG by short hairpin RNA knockdown significantly inhibited cell growth and promoted cell apoptosis in PC cells. We performed bioinformatics analysis to search for the target of MIR155HG. As demonstrated by Luciferase reporter assay, we found that miR‐802, a tumor suppressor in various cancer, is a direct target of MIR155HG. We demonstrated that the tumor‐promoting effects of MIR155HG were contributed by negative regulation of miR‐802 in PC cells. In summary, our results suggest that lncRNA MIR155HG might be applied as a novel diagnostic and therapeutic target for PC. Abstract : MIR155HG expression was significantly upregulated in pancreatic cancer (PC) tumor tissue and cell lines compared with the adjacent normal tissue and cells. Higher MIR155HG expression was positively associated with poor prognosis of patients with PC. Knockdown of MIR155HG remarkably suppressed cell proliferation by inducing cell cycle arrest and promoting cell apoptosis in PC cells. MIR155HG directly bound to the miR‐802, which has been reported to act as a tumor suppressor in various cancers.